Efeitos da administração subaracnoidea em punção única, de cetamina S(+) a 5%, sem conservantes, sobre a medula espinal e as meninges de coelhos - Lima Filho, José Admirço [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Background: Pain relief is one of the tasks of the anesthesiologist . Among the drugs used for this purpose include the ketamine (blocker of N-methyl D aspartate receptor). It can be administered by various routes among which spinal and epidural. Results of clinical and experimental studies have shown that ketamine S (+) was effective in relieving postoperative pain when introduced into the epidural space. Almost nothing is known about his administration in the subarachnoid space. Neurological lesions were described in the medullary tissue of humans and animals when using ketamine S(+) 5% preservative free, the subarachnoid space, the same lesions have been reported in animals with the drug devoid of preservatives. Objective: To evaluate the effects of ketamine S (+) 5% preservative free, administered by the intrathecal route in single puncture , determines on the spinal cord and meninges of rabbits. Method: Twenty young adult female rabbits, weighing 3500-5000 g with entre34 spine length and 38 cm were divided by lot into two groups (G ): 0.9% saline G1 , G2 ketamine S (+) 5% by volume of 5μg per cm column (1,8 μl). After intravenous anesthesia with ketamine and xylazine spinal puncture was performed in S1 - S2 ultrasound guided and injected a random solution. The animals remained in captivity for 21 days under medical observation and were sacrificed by decapitation and removal of the lumbosacral portion of the spinal cord for histologic examination [hematoxylin and eosin (HE)] and immunohistochemistry for glial fibrillary acidic protein (GFAP). Results: No animal showed histological lesions of nerve tissue (roots and cord) and meninges. Conclusions: In this experimental model in rabbits ketamine S (+) 5% preservative free triggered no neurological or histological lesions in the spinal cord and meninges

Introdução O alívio da dor é uma das atribuições do anestesiologista. Dentre os fármacos utilizados com esta finalidade inclui-se a cetamina (bloqueador do receptor Nmetil D aspartato). Ela pode ser administrada por diversas vias dentre as quais a subaracnoidea e a peridural. Resultados de pesquisas clínicas e experimentais mostraram que a cetamina S (+) foi eficaz no alívio da dor pós-operatória quando introduzida no espaço peridural. Contudo, ainda pouco se sabe sobre sua administração no espaço subaracnoideo. Foram descritas lesões neurológicas no tecido medular de seres humanos e animais quando se utilizou a cetamina com conservantes, no espaço subaracnoideo e, as mesmas lesões foram descritas, em animais, com o fármaco desprovido de conservantes. Objetivo: avaliar os efeitos que a cetamina S (+) a 5% sem conservantes, administrada pela via subaracnoidea em punção única, determina sobre a medula espinal e as meninges de coelhos. Método: Vinte coelhos adultos jovens, fêmeas, pesando entre 3500 a 5000 gr com comprimento de coluna vertebral entre 34 e 38 cm foram divididas, por sorteio, em dois grupos (G): G1 solução fisiológica 0,9%, G2 cetamina S (+) 5% em volume de 5μg por cm de coluna (1,8 μl). Após anestesia venosa com cetamina e xilazina foi realizada punção subaracnoidea em S1-S2 guiada por ultrassom e injetada a solução sorteada. Os animais permaneceram em cativeiro por 21 dias sob observação clínica e foram sacrificados por decapitação e retirada a porção lombo-sacral da medula espinal para exame histológico [Hematoxilina e eosina (HE) e imuno-histoquímica para proteína glial fibrilar ácida (GFAP)]. Resultados: nenhum animal apresentou lesão histológica de tecido nervoso (raizes e medula) e meninges. Conclusão: Neste modelo experimental em coelhos a cetamina S (+) 5% sem conservante não desencadeou lesão neurológicas ou histológica na medula espinal e meninges
Effects of ketamine S(+) 5% preservative free, administered by the intrathecal route in single pincture, determines on the spinal cord and meninges of rabbits
Keywords: Anestesicos - Efeito fisiologico; Meninges; Injeções; Medicamentos - Administração